Theorising the Return: From Economic Rationality to Emotional Reflexivity - Bakalova, Maria (Research Papers, 2019)
The research traces the development of theoretical knowledge about the RM within the proposed periodisation. It reveals the increased relevance of new paradigms, in which economic aspects of return are combined with socio-cultural and psychological ones. Economic and non-economic factors bearing on the returnees’ motivation are explicated with a focus on the on emotional reflexivity and non-rationalist motives. It is concluded that the theoretical understanding of return migration increasingly transcends the classic strictly economic accounts with their explanations focused solely on returnees’ economic rationality.
Keywords: Return migration; Economic explanations; Emotional reflexivity